Adam Omelianchuk, Alexander Morgan Capron, Lainie Friedman Ross, Arthur R. Derse, James L. Bernat, and David Magnus reply - Omelianchuk, Adam (The Hastings Center report, 2024)
This letter responds to letters by Garson Leder and by Harrison Lee in the same issue, September-October 2024, of the Hastings Center Report.